2012
DOI: 10.1002/path.3996
|View full text |Cite
|
Sign up to set email alerts
|

Psoriasis in humans is associated with down‐regulation of galectins in dendritic cells

Abstract: 2 ABSTRACT.We have investigated the expression and role of galectin-1 and other galectins in psoriasis and in the Th1/Th17 effector and dendritic cell responses associated with this chronic inflammatory skin condition. To determine differences between psoriasis patients and healthy donors, galectins expression was analyzed by RT-PCR assays in skin samples and specifically on epidermal and peripheral blood dendritic cells by immunofluorescence and flow cytometry.In skin of healthy donors galectins 1, 3 and 9 we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(21 citation statements)
references
References 42 publications
1
19
0
1
Order By: Relevance
“…Previous studies have indicated that Gal-1 expression is diminished at the sites of severe chronic inflammation such as psoriatic skin ( [28] and Krenacs L et al, unpublished data). However, Gal-1 expression in pathological T-cells has not yet been specifically investigated.…”
Section: Diminished Gal-1 Expression Coincides With Decreased Exgal-1mentioning
confidence: 83%
“…Previous studies have indicated that Gal-1 expression is diminished at the sites of severe chronic inflammation such as psoriatic skin ( [28] and Krenacs L et al, unpublished data). However, Gal-1 expression in pathological T-cells has not yet been specifically investigated.…”
Section: Diminished Gal-1 Expression Coincides With Decreased Exgal-1mentioning
confidence: 83%
“…It is important to highlight that in the keratinocytes from normal adult skin, Gal-1 was not evidenced. Remarkably, previous studies in human skin have shown that Gal-1 is not expressed by keratinocytes in normal skin [37] but can be expressed by cells in psoriasis [37,38], cutaneous malignant lesions including squamous cell carcinoma [39], mycosis fungoides [40,41], and melanoma [42], while in keloid tissues, proteome analysis of keloid proteins performed by Ong et al revealed that the expression of Gal-1 is upregulated compared to normal skin [43]. However, the role of Gal-1 in skin lesions is still unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Gal-1, like others galectins, participates in signaling pathways and regulates a variety of biological responses including cell growth, cell-cell and cell-matrix adhesion, cell differentiation, migration, proliferation and survival [31][32][33][34] and plays a critical role in inflammation, angiogenesis, and tumor development and progression [27,33,35,36]. In human skin, Gal-1 has been implicated in psoriasis [37,38] and malignant lesions including cutaneous cancer [39], mycosis fungoides [40,41], and melanoma [42], and scarce studies have shown that the expression of Gal-1 is upregulated in keloid tissue [43]. However, the presence, distribution, and localization of Gal-1 as well as its possible role in benign dermal fibroproliferative tumors such as keloids, have not been completely elucidated.…”
mentioning
confidence: 99%
“…Previous studies have shown that expression of Gal-1 is decreased at sites of chronic inflammation [139]. However, expression of Gal-1 in T-cells has not been studied even though dysfunctional T-cell apoptosis has been documented as a crucial defect in SLE pathogenesis.…”
Section: Role Of Gal-1 In the Pathomechanism Of Human Autoimmune Disementioning
confidence: 99%